2021
DOI: 10.1002/humu.24275
|View full text |Cite
|
Sign up to set email alerts
|

PRPH2 mutation update: In silico assessment of 245 reported and 7 novel variants in patients with retinal disease

Abstract: Mutations in PRPH2, encoding peripherin‐2, are associated with the development of a wide variety of inherited retinal diseases (IRDs). To determine the causality of the many PRPH2 variants that have been discovered over the last decades, we surveyed all published PRPH2 variants up to July 2020, describing 720 index patients that in total carried 245 unique variants. In addition, we identified seven novel PRPH2 variants in eight additional index patients. The pathogenicity of all variants was determined using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 204 publications
4
11
0
Order By: Relevance
“…The prevalence of founder variants was found to be different. In Caucasians, c.424C>T (p.Arg142Trp [13,43,46,49]. Among these variants, c.514C>T was reported in a previous study in Japan [50] and was found in four patients from four families in our cohort.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The prevalence of founder variants was found to be different. In Caucasians, c.424C>T (p.Arg142Trp [13,43,46,49]. Among these variants, c.514C>T was reported in a previous study in Japan [50] and was found in four patients from four families in our cohort.…”
Section: Discussionsupporting
confidence: 64%
“…Previous reports have suggested association between the location of the variant in PRPH2 and clinical phenotype. Specifically, variants are mostly found in the D2 loop [13,43,[46][47][48], which is critical for protein-protein interactions. Variants that cause autosomal dominant RP tend to accumulate between Lys193 and Glu226 [3].…”
Section: Discussionmentioning
confidence: 99%
“…Its autosomal dominant inheritance in macular dystrophies has been reported in other studies [9,14]. Further studies reported on a more generalised rod than cone or cone than rod dysfunction [12,13,15].…”
Section: Discussionsupporting
confidence: 53%
“…Many studies, including this one, have attempted to determine genotype-phenotype correlations of PRPH2, demonstrating a high clinical variability, even within the same family [12,13]. We ana-lysed the genetic and clinical characteristics of two siblings.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether our workflow for HITI-mediated gene construction can be applied to other genes, we targeted mouse Prph2, the second leading cause of AdRP 40,41 . In the grID database in silico finder, three gRNA target sequences with grID scores ranging from 800 to 900 were selected around the 100 bp region of the proximal sequence from the Prph2 5'-UTR (Fig.…”
Section: Prph2 Locusmentioning
confidence: 99%